Distribution and temporal prevalence of Theileria orientalis major piroplasm surface protein types in eastern Australian cattle herds. Issue 8 (26th July 2013) - Eamens, GJ; Bailey, G; Gonsalves, JR; Jenkins, C
<x xml:space="preserve">Abstract</x> Objective To determine the distribution of theilerial types in eastern Australian cattle herds and their changing prevalence in regions of New South Wales (NSW). Design Survey testing of herds in 2010–11 in Queensland (QLD), NSW and Victoria (VIC) where clinical theileriosis was not evident and ongoing surveillance in NSW through laboratory submissions. Methods Blood samples were tested by PCR targeting the Theileria orientalis p32 gene and positive tests were examined for the Ikeda, Chitose and Buffeli types. Survey samples from 516 cattle in 50 herds and diagnostic submissions from 434 suspect field cases in 116 herds were analysed. Results In clinically normal survey cattle, T. orientalis prevalence was high (NSW 23.7%, QLD 56.8%, VIC 34.0%), with variability among regions of each state. Chitose was the most common and widespread type (19.1–43.7% per state), with Buffeli present in all states at a lower prevalence (10.8–24.8% per state). Ikeda was detected in three of five regions in QLD (North, South and South East; prevalence 3.4–15.4%), only one of the surveyed regions in NSW (North Coast; prevalence 74.2%) and in only one animal in VIC. Evidence of clinical disease and laboratory confirmation of Ikeda infection in diagnostic submissions were predominant in several NSW regions, with increasing numbers of affected herds particularly in the coastal Mid‐Coast and Cumberland areas. Conclusions In those regions where prior evidence of theileriosis was uncommon, Ikeda infection was evident in a limited number of NSW regions and multiple regions in QLD. However, clinical disease has continued to become widespread in NSW and VIC, involving Ikeda strains in many regions.